Spiritual Needs in Cancer Patients: A Narrative Review - Iyus Yosep; Rohman Hikmat; Ai Mardhiyah (Science Midwifery, 2022)
Cancer is a life-threatening disease and causes physical, psychological, and spiritual problems for sufferers. The fulfillment of spiritual needs is one of the important things to improve the quality of life of cancer patients. However, health services still focus on fulfilling the physical aspect. So comprehensive data is needed regarding the spiritual needs of cancer patients. The purpose of this study was to comprehensively explore the fulfillment of spiritual needs in cancer patients. This study uses the Narrative Review method. Literature review through Ebsco, Pubmed, Science Direct, Sage Journals, and Google Scholar databases. The keywords used in English are "Spiritual needs OR Spirituality OR spiritual care" AND "cancer" AND "patient". While the keywords in Indonesian used are "spiritual needs OR spirituality OR spiritual care" AND "cancer" AND "patient". The criteria for articles in this study are full text, free access, research articles, review articles, in English and Indonesian, population and samples of cancer patients, and the publication period of the last 10 years (2013-2022). We found 10 articles with different aspects of fulfilling spiritual needs. 4 articles on aspects of the meaning of life and purpose, 2 articles on aspects of strength in belief, 3 articles on spiritual aspects with peace, hope, and gratitude, and 1 article on aspects of connection with the category of social support. There are 4 aspects of fulfilling spiritual needs that are felt by cancer patients, namely the meaning of life and purpose, strength in belief, spirituality with peace, hope, and gratitude, and connection with the category of social support.